Bird Interspecific Brood Parasitism Record in the Third Century - Dongyang Li; Yimei Zhang; Canwei Xia (Birds)
The phenomenon of interspecies brood parasitism, characterized by parasitic birds depositing their eggs within the nests of unrelated host species for subsequent hatching and rearing, represents a pivotal aspect of ornithological research, owing to its profound implications for the coevolutionary dynamics between host and parasite species. Among the myriad of avian brood parasites, the Common Cuckoo (Cuculus canorus) stands out due to its expansive geographical range and diverse array of host species, thereby underscoring its significance in the context of parasitism studies. Drawing upon historical records dating back to the Three Kingdoms period (220–280 AD) in China, this study delves into the annals of avian brood parasitism, uncovering instances of parasitic behavior attributed to the Common Cuckoo. Through a meticulous analysis of these ancient narratives, coupled with an examination of the ecological and morphological attributes of the birds involved, we confirm the parasitization of Barn Swallows (Hirundo rustica) by Common Cuckoos. This finding underscores the existence of a long-standing coevolutionary relationship between these two species, extending over nearly two millennia. Remarkably, the record under scrutiny, with its precise temporal, geographical, and taxonomic specifications, emerges as a potential candidate for the earliest documented instance of Common Cuckoo brood parasitism in Chinese historical records. As such, it provides invaluable insights into the historical ecology of avian parasitism and underscores the need for further interdisciplinary research to unravel the complexities of host–parasite interactions across time and space.